Mitigating financial mismanagement: Insights from Caliph Umar’s Governance - Masruki, Rosnia (Proceeding International Conference on Accounting and Finance, 2024)
The practice of good governance is often associated with combating corruption. Conversely, the failure of governance leads to significant issues that tarnish accountability and erode public trust in an institution. Despite its undeniable importance, governance also poses significant challenges in religious institutions, notably the zakat system, have expanded to address socio-economic issues, yet results may vary. This study examined Islamic history, Caliph Umar ibn Abdul Aziz's brief but impactful reign featured the baitulmal, eliminating asnaf groups eligible for zakat. The study revealed that Caliph Umar’s governance strategy (siasah shar’iyyah) is rooted in Shariah-based maslahah (goodness) and effectively prevents mafsadah (harm). The initiative strategic governance involved through creating a conducive environment for production growth, fostering agricualtural and busines sectors, strengthening zakat institution and baitulmal empowerment as well as prioritizing social protection measures. The principles of maslahah and mafsadah are in alignment with the tenets of Maqasid Shariah, providing insights into combatting mismanagement through the reinforcement of governance mechanisms. While the study draws from extensive literature mainly on Caliph Umar ibn Abdul Aziz, its reliance on secondary data sources limits the depth of analysis and direct control over data quality.